KARYAWAN GENERASI MILENIAL: GRIT DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Hafidz Estu Primanda; Sowanya Ardi Prahara (Jurnal Psikohumanika, 2022)
Abstract Organizational citizenship behavior is part of the behavioral aspects that millennial generation employees need to have, because it can provide opportunities for millennial generation employees to develop, show their best abilities and give good appreciation to the organization. This is why grit is so important for millennial generation employees, because grit helps overcome obstacles and challenges to achieve the results it wants. This study aims to determine the relationship between grit and organizational citizenship behavior in millennial generation employees. The subjects of the study were 120 employees between the ages of 22 and 42 who had at least one year of work experience. The sampling technique in the study was to use the purposive sampling method. When collecting data this study used the Grit Scale on the Organizational Citizenship Behavior Scale. The data analysis technique used in this study is product-moment correlation. The results showed that there is a significant positive relationship between grit and organizational citizenship behavior in millennial generation employees. Keywords: Grit, organizational citizenship behavior, millennial generation employees